Teacher Strategy in Teaching English During Covid-19 Pandemic for the Eighth Grade Students at SMP Baitul Arqom Balung - Shalahuddin, Aklil; Devanti, Yeni Mardiyana; Nurkamilah, Nurkamilah (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Corona virus, also known as COVID-19, has been causing havoc around the world since the end of 2019. The pandemic situation has completely replaced the way of teaching English method from face-to-face learning into online teaching. This research aims to investigate the teachers’ strategies in using online learning platform and the challenges in implementing their strategies during Covid-19 pandemic through online learning platforms". The design of this study was qualitative approach. This study involves English teacher of SMP Baitul Arqom Balung as the inteviewee. The data was collected through documentation and interview. Based on observation the researcher found that the online learning application used in SMP Baitul Arqom Balung was a WhatsApp, Google Form, Zoom, Google classroom. In conclusion, the researcher found strategies had applied by student teachers in teaching English online. Those strategies as follows: Explaining the material by using several devices, checking of students’ understanding, and giving the assignment.